Panel depicting a couple seated on a circular throne and surrounded by female attendants - Temples of India Project Team (Jio Institute, 2024)
Sculptural panel depicting a couple (likely royal, based on their size and posture) seated on a circular throne and surrounded by female attendants. The scene depicts the couple admiring each other, in a moment of shringar rasa (romantic love). The central figure of the man is seated in the lalitasana posture. He is caressing his partner’s chin with his left hand while holding a flower in his right hand, offering it to her. The lady is resting her right hand on the left thigh of the man and her head is tilted upwards, as he looks into her face. One of the female attendants is seated on the right thigh of the central male figure.